Perbandingan Tindakan Massage Counterpressure dan Pemberian Dark Chocolate terhadap Penurunan Nyeri Haid (Dismenorea) - Rindang Fitriana Ulfa; Agus Suwandono; Kamilah Budhi (Jurnal Keperawatan Silampari, 2019)
The purpose of this study was to see the comparison between the administration of Massage Counterpressure and the provision of dark chocolate to reduce menstrual pain (dysmenorrhoea). The design uses a quasi-experimental design with two groups of pretest and posttest with control group design. The results showed that in the dark chocolate and anti-pain medication group, massage counterressure and anti-pain medicine obtained Ï value of 0,000. there are significant differences before and after the administration of action. The results of the man whitney test found that there were differences between the 2 groups with a value of Ï value of 0,000. Conclusion, there is a difference of influence between the dark chocolate group and the counterpressure massage group on the intensity of menstrual pain. Giving 100 grams of dark chocolate for 2 days and anti-pain medication is more effective than a 20-minute counterpressure massage for 2 days and anti-pain medication for menstrual pain intensity. Keywords: Dark Chocolate, Massage counterprssure, Menstrual pain